2020
DOI: 10.3390/nu12020527
|View full text |Cite
|
Sign up to set email alerts
|

Postural Balance Effects Associated with 400, 4000 or 10,000 IU Vitamin D3 Daily for Three Years: A Secondary Analysis of a Randomized Clinical Trial

Abstract: Vitamin D supplementation is proposed as a fall prevention strategy, as it may improve neuromuscular function. We examined whether three years of vitamin D supplementation (400, 4000 or 10,000 IU daily) affects postural sway in older adults. Three hundred and seventy-three non-osteoporotic, vitamin D-sufficient, community-dwelling healthy adults, aged 55–70 years, were randomized to 400 (n = 124), 4000 (n = 125) or 10,000 (n = 124) IU daily vitamin D3 for three years. Sway index was assessed at baseline, 12-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In the same study, areal BMD did not change irrespective of the dose [43]. Along this line, postural sway was not affected between daily doses of vitamin D of 400, 4000 and 10,000 [44], vitamin D daily equivalent of 5700 IU was not different from 800 IU in terms of muscle strength and balance [45], changes in muscle strength and mass were not different in the 40,000 IU/week vitamin D2 (equivalent to 5700 IU/day) and placebo groups [46], whilst 1000 IU/day increased lower limb muscle strength [47]. In a systematic review and meta-analysis published in 2011, the conclusion was that daily doses of 800 to 1000 IU consistently demonstrated beneficial effects on muscle strength and balance [48].…”
Section: Fallsmentioning
confidence: 65%
“…In the same study, areal BMD did not change irrespective of the dose [43]. Along this line, postural sway was not affected between daily doses of vitamin D of 400, 4000 and 10,000 [44], vitamin D daily equivalent of 5700 IU was not different from 800 IU in terms of muscle strength and balance [45], changes in muscle strength and mass were not different in the 40,000 IU/week vitamin D2 (equivalent to 5700 IU/day) and placebo groups [46], whilst 1000 IU/day increased lower limb muscle strength [47]. In a systematic review and meta-analysis published in 2011, the conclusion was that daily doses of 800 to 1000 IU consistently demonstrated beneficial effects on muscle strength and balance [48].…”
Section: Fallsmentioning
confidence: 65%
“…Many studies which have utilized the Biodex Biosway™ for assessment of postural sway or compared the Biodex Biosway™ to other devices have reported that this is a reliable assessment tool [8][9][10][11][12][13][14][15]. However, on closer examination, these same studies have supported this claim by citing reliability studies which were actually performed on a separate hardware system designed for dynamic posturography, the Biodex Balance System [16][17][18].…”
Section: Introductionmentioning
confidence: 99%